INSTAGRAMABLE PILGRIMAGE: SPIRITUALISM, CONSERVATISM AND COMMODIFIED RELIGION ON INDONESIAN CELEBGRAMS POSTS - Fauzia, Amelia; Mojopahit, Haryo (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
Economic development, technological advances, infrastructure improvements, and religious awakening have increased the practice of religious journey (pilgrimage), including among Muslims in Indonesia. Young celebrities have actively shared their religious journeys on social media as self-expression and religious testimony. These uploads are religion online’ that provide religious information to the public, especially to their followers. This article is a qualitative study on the phenomenon of religious travel in contemporary Indonesia. This study takes the case of three Muslim female celebrities who are public figures in Indonesia. By analyzing their uploads related to religious travel (or what we call instagrammable pilgrimages) on Instagram during the pandemic and post-pandemic period (July 2021 to April 2023), we find that the phenomenon of religious travel can be examined in terms of its impact on human behavior and that an increase in Islamic religiosity can be observed and registered in the space of spiritualism and the use of religion for the economy, rather than simply an increase in conservatism.